Effect of price difference, social hierarchy and indigenous social norm on fair price perception; analyzing on role of financing source. - Mohsen Nazari; Hanieh Fathi (مطالعات رفتار مصرف کننده., 2019)
Numerous studies indicate that consumers will not be encouraged to loyalty and repurchase as long as the sellers do not act in the fair market, hence many factors affect consumers' fair perception. The purpose of this study is to investigate the effect of hierarchical and indigenous price differences and social norms on perceptions of fair pricing by expressing the role of financing source. The objective view is regarded as applied research, the method of research is descriptive and in terms of data collection method it is field library type. This research is based on a factorial experimental design with four different role-playing scenarios distributed in a questionnaire among Parsian International Hotel customers. The results of the study of data collected from the 240 questionnaires and testing the hypotheses show that there is no significant difference between the effect of price difference 100000 and 1500000 rials on fair perception, but there was a significant difference between the impact of hierarchical and indigenous social norms on perceptions of fairness. The results of factor analysis of variance also showed that the interactive effect of the source of financing was approved by the individual or organization in relation to social norm and fair perception, but the interactive effect of the source of financing by the individual or organization in relation to the difference in price and the fair perception was not confirmed.